Variations of Gadung Tuber Extract (Discorea hispida) and Boric Acid in Gel Form as Cockroach Bait (Blatella germanica) - Cahyo, Cahyo Dwi Prakoso; Eko, Sarjito Eko Windarso; Iswanto, Iswanto; Lucky, Lucky Herawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Cockroaches are disease vectors that pose health and aesthetic problems. Traditional control methods use insecticides, which are becoming ineffective and environmentally harmful due to residue. An alternative method involves gel bait with plant-based insecticides, such as grading tubers, which are toxic to insects. This research aims to determine the optimal combination of grading tuber extract and boric acid in gel bait by calculating LC50 and LT50. Conducted at the Yogyakarta Health Polytechnic Vector and Animal Control Laboratory in February-March 2023, the study used a proper experimental design with a post-test-only control group. Five treatments were tested with five repetitions each, using 125 female cockroaches (Blatella germanica) selected via purposive sampling. Mortality data were analyzed using One Way Anova, LSD tests (p-value < 0.05), and probit regression. Results showed significant differences in mortality rates among treatments (p-value = 0.000). Variation C had the highest mortality rate, while variation B was the most effective, with an LC50 of 7.227 g. LT50 values were 99.237 hours for 5 g, 93.797 hours for 10 g, and 73.463 hours for 15 g. This study concludes that gel bait with grading tuber extract and boric acid is a promising alternative for cockroach control.